Raman Laser with a Singly Resonant Cavity: Theoretical Model and Experiment - Voitikov, Sergei Viktorovich; Chulkov, Ruslan; Markevich, Vasyli; Orlovich, Valentin; Khanh, Do Quoc; Minh, Pham Hong; Tu, Nguyen Xuan (Communications in Physics, 2018)
A semiclassical theoretical model of a Raman laser possessing a cavity which is resonant at the Stokes wavelength and not resonant at the pump wavelength has been developed. The wave equations describing evolution of amplitudes of the pump and Stokes pulses in the Raman cavity have been derived. Results of the theoretical modeling have been analyzed for conditions of an experiment with the Raman laser on barium nitrate crystal under the nanosecond pulse pump. Numerically calculated energy characteristics of the Raman laser as well as space-time dynamics of the Stokes generation have been demonstrated to be in reasonable agreement with the experiment.